Branding estratégico para el reconocimiento de marca de Corax Capacitaciones de la ciudad de Ambato - Erika Lizbeth, Micolta Chicaiza (2024)
This study focuses on the thorough evaluation and understanding of marketing strategies employed in brand management, addressing three crucial dimensions: Brand Consistency Strategy, Communication Strategy, and Promotion Strategy, with a particular emphasis on Below The Line (BTL) strategy. The Brand Consistency Strategy highlights the significant importance of maintaining a uniform and coherent message across all communication channels. This approach aims to ensure that the brand's identity and values are consistently conveyed, building trust and recognition among the audience. The Communication Strategy focuses on the effective integration of marketing strategies, particularly emphasizing a presence in digital media and social networks. The interconnection of these channels enables smoother and more cohesive communication, maximizing the brand's impact in an increasingly relevant digital environment. Finally, the Promotion Strategy, specifically through the BTL strategy, is oriented towards specific tactics aimed at creating personalized experiences for consumers. These tactics may include events, direct promotions, local sponsorships, among others, seeking a more direct and tangible connection with the target audience. The detailed analysis of these dimensions not only provides a deep insight into how brands manage their presence in the market but also emphasizes the importance of consistency, integration, and personalization in marketing strategies. Together, these elements contribute to building a holistic understanding of how brands interact and position themselves in the competitive landscape of the current market. This comprehensive approach is essential for the long-term success and sustainability of a brand in a dynamic and constantly evolving business environment.